2020
DOI: 10.3390/medicina56090472
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic of Temporomandibular Disorders and Other Facial Pain Conditions—Narrative Review and Personal Experience

Abstract: Temporomandibular disorders are complex dysfunctions of masticatory muscles and temporomandibular joints. Their symptoms affect more than 40% of the population and their prevalence is rising. It is important to establish a unified protocol for this specialistic examination. This review describes the authors’ own longstanding experiences and the discrepancies in the current literature regarding this topic as well as a detailed procedure of diagnosing temporomandibular disorders including the leading but often u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Temporomandibular disorders (TMDs) are a group of disorders involving pain and dysfunction of the temporomandibular joint (TMJ) and masticatory muscles [ 1 ]. The prevalence of TMDs is approximately 40% [ 2 ], with higher rates in individuals aged 20–40 years and in women [ 1 , 3 , 4 ]. The main symptoms of TMDs include pain in the face and TMJ area, the difficulty of mandibular movement, and TMJ noises during mandibular movement [ 1 ], which affects the quality of life for many patients.…”
Section: Introductionmentioning
confidence: 99%
“…Temporomandibular disorders (TMDs) are a group of disorders involving pain and dysfunction of the temporomandibular joint (TMJ) and masticatory muscles [ 1 ]. The prevalence of TMDs is approximately 40% [ 2 ], with higher rates in individuals aged 20–40 years and in women [ 1 , 3 , 4 ]. The main symptoms of TMDs include pain in the face and TMJ area, the difficulty of mandibular movement, and TMJ noises during mandibular movement [ 1 ], which affects the quality of life for many patients.…”
Section: Introductionmentioning
confidence: 99%
“…Temporomandibular disorders (TMD) are a group of conditions that cause pain and dysfunction of the masticatory muscles, temporomandibular joint (TMJ), and the surrounding musculoskeletal structures (1). Being the third most prevalent social dental disease, TMD affects about 10-15% population across the world and the incidence is still rising (2,3). Typical symptoms of TMD include local pain, limited mandibular movement, and TMJ sounds during movement (4).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, temporomandibular disorders (TMD) is a collective term consisting of all the problems regarding the temporomandibular joint and related musculoskeletal structures. It is the third most prevalent social dental disease (Małgorzata et al, 2020) and has been reported to be associated with psychosocial factors (Rollman & Gillespie, 2000), such as previous trauma, stress symptoms, psychosocial impairment, and catastrophizing. The coronavirus pandemic, as a Public Health Emergency of International Concern, might also have an impact on TMD patients.…”
Section: Introductionmentioning
confidence: 99%